Medical Evidence Influence on Inpatients and Nurses Pain Ratings Agreement - Boaz Gedaliahu Samolsky Dekel; Alberto Gori; Alessio Vasarri; Maria Cristina Sorella; Gianfranco Di Nino; Rita Maria Melotti (Pain Research and Management)
Biased pain evaluation due to automated heuristics driven by symptom uncertainty may undermine pain treatment; medical evidence moderators are thought to play a role in such circumstances. We explored, in this cross-sectional survey, the effect of such moderators (e.g., nurse awareness of patients’ pain experience and treatment) on the agreement between n=862 inpatients’ self-reported pain and n=115 nurses’ pain ratings using a numerical rating scale. We assessed the mean of absolute difference, agreement (κ-statistics), and correlation (Spearman rank) of inpatients and nurses’ pain ratings and analyzed congruence categories’ (CCs: underestimation, congruence, and overestimation) proportions and dependence upon pain categories for each medical evidence moderator (χ2 analysis). Pain ratings agreement and correlation were limited; the CCs proportions were further modulated by the studied moderators. Medical evidence promoted in nurses overestimation of low and underestimation of high inpatients’ self-reported pain. Knowledge of the negative influence of automated heuristics driven by symptoms uncertainty and medical-evidence moderators on pain evaluation may render pain assessment more accurate.